TRANSFORMATIONS IN THE JOURNALISTIC INDUSTRY AND THE NEED FOR A NEW BUSINESS MODEL: AVNA - Fernandes RODRIGUES, Daniele; Ferreira Hygino NUNES, Milena; Henrique Medeiros de SOUZA, Carlos (LINKSCIENCEPLACE, 2026)
The technological revolution that has occurred in recent times has impacted life in society, the business world, and even more intensely and particularly the business of the journalistic industry, which is having to reinvent itself after the radical transformation undergone in its means of distribution And post-popularization circulation of the internet and the emergence of cyberspace. Due to this scenario and added the current moment of Brazilian economic crisis, it becomes even more relevant to seek new forms of business, to consume less resources, to add more value and can mainly become self-manageable, that is, a system that can Maintain and continue to operate with the smallest possible structure, even if it initially requires operating support. The purpose of this article is to reflect on the transformations in the journalistic industry, proposing new ideas about a journalistic business model through a self - managing news virtual environment - AVNA. A model that supports efforts to continuously improve journalistic quality, with a consequent increase in advertising and service revenues, continuous investments in intellectual capital and an increase in intangible wealth. This research is part of the research center CATI - Communication, Administration and Information Technology -, which belongs to the GETIC (Group of Studies on Education, Communication and Information Technology, linked to CNPq), the Postgraduate Program in Cognition and Language of the Universidade Estadual do Norte Fluminense (UENF).